Angiosarcoma of the Scalp and Face: A Dosimetric Comparison of HDR Surface Applicator Brachytherapy and VMAT. (25th August 2020) - Mitra, Devarati; Pei, Yaguang; Buzurovic, Ivan; Devlin, Phillip M.; Thornton, Katherine; Raut, Chandrajit P.; Baldini, Elizabeth H.; Lam, Miranda B.
Abstract : Purpose . Angiosarcoma of the face and scalp is a rare disease with high rates of recurrence. The optimal treatment approach is not well defined. This study presents a dosimetric comparison of high-dose-rate surface applicator (HDR-SA) brachytherapy to volumetric-modulated arc therapy (VMAT). Methods . Between 2011 and 2018, 12 patients with primary or recurrent angiosarcoma of the face or scalp were treated with HDR-SA brachytherapy using CT-based planning at our institution. For comparison, deliverable VMAT plans for each patient were generated, and dose distribution was compared to the delivered HDR-SA brachytherapy plans. Results . Both VMAT and HDR-SA brachytherapy plans delivered good coverage of the clinical target. However, the dose distribution of VMAT was significantly different from HDR-SA brachytherapy across a variety of parameters. Mean doses to the lacrimal gland, orbit, lens, and cochlea were significantly higher with HDR-SA brachytherapy vs. VMAT. Brain Dmax, V80%, and V50% were also significantly higher with HDR-SA brachytherapy. Conclusions . There may be dosimetric advantages to VMAT over HDR-SA brachytherapy for many patients. However, individual tumor location, patient anatomy, and treatment reproducibility may result in HDR-SA brachytherapy being the preferred technique in a subset of patients. Ultimately, a personalized approach is likely to be the optimal treatment plan.